Real-world experience with CLAIRYG® 50 mg/mL (intravenous immunoglobulin) in children under 12 years with primary immunodeficiency or immmune thrombocytopenia: a post-approval safety study - Mahlaoui, Nizar; Fouyssac, Fanny; Mazingue, Françoise; Mallebranche, Coralie; Barthez-Toullec, Malika; Denti, Lamia; Ruhier, Kalaivani; André-Bonnet, Marie-Hélène; Marie-Cardine, Aude; Aladjidi, Nathalie; Stephan, Jean-Louis (Frontiers in Pediatrics, 2023)
This study presents the results of a real-life, multicenter, prospective, post-approval safety evaluation of Clairyg® 50 mg/mL, a 5% intravenous immunoglobulin (IVIg) liquid, in 59 children (aged<12 years) with primary immunodeficiency diseases (PID) (n=32) or immune thrombocytopenia (ITP) (n=27) in France. The primary objective of the study was to assess the safety and tolerability of Clairyg®, recording all serious and non-serious adverse events (AEs), whether related (rAEs) or not related to the product. Secondary objectives aimed at evaluating the administration of Clairyg® under routine conditions and the available efficacy data to better document the benefit/risk ratio in this pediatric population. An exploratory objective was added to evaluate the potential factors associated with the occurrence of rAEs.Patients received Clairyg® according to the approved dosage under normal conditions of prescriptions over a median follow-up period of 11.8 months. A total of 549 infusions (PID: n=464 and ITP: n=85), were administered, of which 58.8% were preceded by premedication. The most frequent rAEs were headache, vomiting, and pyrexia in both indications. Most of them were considered non-serious and mild or moderate in intensity. A severe single rAE was observed (aseptic meningitis) in a 4-year-old girl presenting with chronic ITP. The exploratory multivariate analysis of potential co-factors showed that the occurrence of rAEs is significantly linked to high IVIg doses and possibly to female gender.The annualized rate of serious bacterial infections was 0.11 for patients with PID. For patients with ITP, 74.1% experienced at least one bleeding episode during the follow-up, mostly a cutaneous one, and none had gastrointestinal, genitourinary, or central nervous system bleeding.In conclusion, Clairyg® was well tolerated and allowed for control of serious bacterial infection in PID and serious bleeding in ITP, which are the main complications in these respective pediatric disorders. No new safety signal was detected in children less than 12 years-old in real-life conditions of use.